A theoretical and experimental study of advanced control methods to suppress vibrations in a small square plate subject to temperature variations - Shimon, P.; Hurmuzlu, Y. (Journal of sound and vibration, 2007)
In this paper, we seek to develop an efficient controller for vibration reduction in a small square plate clamped on all edges. The plate mimics a piece of an aircraft's skin. Small plate size results in higher natural frequencies than normally investigated in literature. Such high-frequency systems are more susceptible to time delays. In addition, the control system must be able to operate over a wide range of temperatures, a requirement for in-flight vibration suppression systems. We investigate two methodologies (sliding mode control, and an adaptive H ∞ control) for control over a wide range of temperatures. Theoretical and experimental studies are conducted and produced varying results. The best theoretical and experimental results are obtained with the adaptive H ∞ controller.